FPGA implementation of a coprocessor architecture for random data generation and encryption - Manoj Kumar (International Journal of Reconfigurable and Embedded Systems (IJRES), 2026)
Coprocessors are designed to perform some specific tasks to enhance system performance and speed. Information security is the main focus in internet of thing (IoT), cryptography, and cybersecurity applications. In this work, a coprocessor architecture is designed to generate 4-bits of random data and perform encryption. Coprocessor architecture uses true random number generator (TRNG) and pseudo-random number generator (PRNG) architectures to generate random data. Modified linear feedback shift register (LFSR)-based PRNG and modified transition effect ring oscillator (TERO) and ring oscillator-based TRNG architectures are designed and implemented for performing encryption. A serial-in-parallel-out (SIPO) shift register circuit is used to generate 4-bit random data. A 15-bit instruction word is assigned to coprocessor architecture to perform its task. The coprocessor architecture is designed using VHSIC Hardware Description Language (VHDL) and implemented on an Artix-7 field programmable gate array (FPGA). All simulation and synthesis results of the proposed coprocessor architecture are obtained by the Xilinx Vivado 2015.2 tool. Coprocessor architecture efficiency (throughput (Mbps)/LUTs) is 2.31, and it operates at a 100 MHz clock.